2021
DOI: 10.1186/s42155-021-00243-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of Shockwave intravascular lithotripsy for the treatment of symptomatic and severely calcified superior mesenteric artery stenosis

Abstract: Background We present the use of intravascular lithotripsy as a treatment for highly calcified superior mesenteric artery stenosis. Case presentation A 67-year-old diabetic man had chronic postprandial abdominal pain and weight loss. Computed tomography angiography revealed highly calcified stenosis of the superior mesenteric artery. Selective angiography confirmed severe stenosis. A Shockwave lithotripsy balloon catheter was successfully used via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Emissions of electrical discharges are compatible with pacemakers and defibrillators. 9 This intriguing technology has been confirmed with satisfactory results in both the coronary field 5 and peripheral field with the DISRUPT PAD II 6 and III 10 studies, which showed promising results of 100% of primary patency in 30 days, 80% in 60 days, and 70% in 12 months in the absence of distal embolization, thrombosis, or vessel perforation.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Emissions of electrical discharges are compatible with pacemakers and defibrillators. 9 This intriguing technology has been confirmed with satisfactory results in both the coronary field 5 and peripheral field with the DISRUPT PAD II 6 and III 10 studies, which showed promising results of 100% of primary patency in 30 days, 80% in 60 days, and 70% in 12 months in the absence of distal embolization, thrombosis, or vessel perforation.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, a stent (covered or uncovered) was placed in 82% of the vessels. Sogomonian 11 and Balboa Arregui 9 did not report stent or stent-graft implantation after PTA with Shockwave TM IVL. The technical success, which was defined as the resolution of the stenosis without hemodynamic residual stenosis, absence of vessel dissection, thrombosis, and embolization was reached in all cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, 4 articles reporting the use of IVL in the splanchnic circulation have been published. [17][18][19][20] Khan M et al demonstrated the use of the IVL system in two cases. The first patient presented with a high grade stenosis of the superior mesenteric artery (SMA) with severe calcifications that was treated through IVL application, followed by stenting.…”
Section: Discussionmentioning
confidence: 99%
“…18 Arregui B et al used the IVL system to modify and dilate a calcified lesion at the ostium of the SMA, using single shockwaves emitted by the distal emitter of the IVL balloon to facilitate entry of the balloon through the lesion, followed by application of shockwaves through the full length of the balloon to fully dilate the stenosis. 19 Lastly, Sogomonian R et al utilized the IVL system to dilate an occlusive lesion of the SMA after insufficient dilation with a plain balloon. 20 As such, this technology also appears to be promising in both renal and splanchnic arteries, but larger trials are needed to confirm the safety and effectiveness of using the IVL system in these patients.…”
Section: Discussionmentioning
confidence: 99%